1998
DOI: 10.1111/j.1365-2621.1998.tb15736.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of Acetylated Chickpea Proteins

Abstract: Functional properties were investigated on chickpea proteins acetylated at 6 and 49% of the -amino groups of lysine. In water and in 0.25M NaCl solutions, acetylated chickpea proteins (ACP) were more soluble at high pH (pHϾ8), but less soluble at low pH (pH 2-7), than native chickpea protein (NCP). The solubility of ACP and NCP was reduced in 0.25-0.75M CaCl 2 solutions. Acetylation increased the water and oil absorption capacity of ACP. ACP also had higher emulsion capacity than that of NCP, but acetylation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 50 publications
5
15
0
Order By: Relevance
“…This could possibly be due to the different nature of protein in Jatropha seed cake compared with that in Moringa seeds or other seeds for which higher solubility of proteins in NaCl has been reported in the literature. The results obtained in the present study are similar to those obtained by Bera and Mukherjee23 for rice bran proteins and by Liu and Hung24 for chickpea proteins. These authors showed decreased solubility in the presence of NaCl.…”
Section: Resultssupporting
confidence: 92%
“…This could possibly be due to the different nature of protein in Jatropha seed cake compared with that in Moringa seeds or other seeds for which higher solubility of proteins in NaCl has been reported in the literature. The results obtained in the present study are similar to those obtained by Bera and Mukherjee23 for rice bran proteins and by Liu and Hung24 for chickpea proteins. These authors showed decreased solubility in the presence of NaCl.…”
Section: Resultssupporting
confidence: 92%
“…The ESI of the chickpea protein isolates was lowest at pH 4.0, and increased slightly when the pH was adjusted to a value higher than 4.0, but markedly increased at pH 3.0, which was similar to EAI at pH 3.0. This result was in agreement with those reported earlier for chickpea (Liu and Hung 1998b) and Dolichos lablab bean (Lawal 2005). Contrary to EAI, GCPI presented a lower ESI than ZCPI over a pH range of 4.0–8.0.…”
Section: Resultssupporting
confidence: 94%
“…When the pH was above the isoelectric point, the emulsifying capacity of chickpea protein isolates increased with the enhancement of pH, and the difference magnitude corresponded to their solubility (Fig. 1), which is in agreement with those reported earlier for chickpea (Liu and Hung 1998b), soybean (Crenwelge et al. 1974) and beach pea (Chavan et al.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…I n the food industry, acetylation with acetic anhydrides, one of the most common chemical modifications used for proteins, has been shown to be a very powerful tool for improving the functional properties of many plant proteins, including soy protein (Franzen and Kinsella 1976a;Umeya and others 1981), leaf protein (Franzen and Kinsella 1976b), sunflower (Kabirrullah and Wills 1982), cottonseed (Rahma and Narasinga Rao 1983), winged bean (Narayana and Narasinga Rao 1984), oat (Ma 1984), faba bean (Muschiolik and others 1987;Krause and others 1996), rapeseed (Gruener and Ismond 1997), chickpea (Liu and Hung 1998), and mung bean (Ei-Adawy 2000).…”
Section: Introductionmentioning
confidence: 99%